2019
DOI: 10.1080/09658211.2019.1705351
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for adult age-invariance in associative false recognition

Abstract: A M (2019) Evidence for adult age-invariance in associative false recognition. Memory. pp. 1-15.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 87 publications
(155 reference statements)
0
6
0
Order By: Relevance
“…We also acknowledge that our method included a prior cued-recall test with substantial intrusion errors that could have impacted 5AFC performance (Panuswan et al, 2020). It is possible that the cued-recall test altered underlying memory representations in a way that affected recognition performance, such as by reinforcing recall intrusions errors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also acknowledge that our method included a prior cued-recall test with substantial intrusion errors that could have impacted 5AFC performance (Panuswan et al, 2020). It is possible that the cued-recall test altered underlying memory representations in a way that affected recognition performance, such as by reinforcing recall intrusions errors.…”
Section: Discussionmentioning
confidence: 99%
“…1 Older adults have been reported to have deficits in accuracy of RCJs (e.g., Kelley & Sahakyan, 2003). They are prone to being falsely confident when making a recognition memory false alarm (e.g., Chua et al, 2009; Dodson et al, 2007; Fandakova et al, 2013, 2018; Shing et al, 2009), especially in tasks designed to produce memory errors (e.g., Tun et al, 1998; but see Panuswan et al, 2020). In source monitoring experiments, they are less likely to reconsider inaccurate source memory attributions by searching for disconfirming evidence (Henkel et al, 1998; Johnson, 2006).…”
Section: Age Differences In Memory Errorsmentioning
confidence: 99%
“…First, we examined the effects of warnings and guessing the CI from NCA and C+A lists in a sample of older adults. Healthy aging is associated with preserved automatic processes and declines in controlled processing, and older adults have equivalent or elevated false memories compared to younger adults (e.g., Schacter et al, 1997;Balota et al, 1999;Liu and Cao, 2002;Huff and Aschenbrenner, 2018;Pansuwan et al, 2020). Older adults are also less likely than younger adults to benefit from a warning (McCabe and Smith, 2002), and there is evidence of different lifespan time courses for reliance on taxonomic (i.e., categorical) and associative or thematic information (Mirman et al, 2017;Belacchi and Artuso, 2018).…”
Section: Decomposing Semantic and Associative Similaritymentioning
confidence: 99%
“…There are reasons to predict that older adults would be more susceptible to pragmatic inferences than their younger counterparts. First, previous studies on false memory have shown that older adults are misled more often, and have higher false alarm rates, than young adults in eyewitness testimony paradigm (LaVoie, Mertz, & Richmond, 2007;Roediger III & Geraci, 2007), in Deese-Roediger-McDermott (DRM) paradigm (Dehon & Br edart, 2004;Dennis, Kim, & Cabeza, 2008;Pansuwan et al, 2020) and in pragmatic inference paradigm (McDermott & Chan, 2006). Second, this age-related susceptibility to pragmatic inference could be modulated by the content of advertisement.…”
Section: Introductionmentioning
confidence: 99%